Penyuluhan Mekanisme Gadai Bank Syariah Indonesia Pada SMK Swasta PAB 12 Saentis - Putri Nazli (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The development of the sharia financial system is marked by the establishment of various sharia institutions and the issuance of various sharia-based financial instruments. Apart from banks which have the function of collecting and distributing funds to the community. However, banks also have the function of providing services such as pawning. Bank Syariah Indonesia is one of the banks that has a gold pawn product which is considered successful because it continues to increase every year. Sharia gold pawn financing is a product of channeling funds in the form of loans based on the qard principle with collateral of valuables in the form of gold as collateral for the customer's money. In providing financing to customers, there are several process stages that must be carried out by the Bank and Bank Syariah Indonesia also sets rental fees for gold pawn products that are quite cheap compared to other institutions. In this dedication, I explain the mechanism of gold pawning products at Bank Syariah Indonesia. The aim is for the public to become more familiar with the services and operations of Sharia Banks.